Nematode infestation and N-effect of legumes on soil and crop yelds in legume-sorghum rotations - Bado, V.; Sawadogo, A.; Thio, B.; Bationo, A.; Traoré, K.; Cescas, M. (Scientific Research Publishing, Inc., 2011)
The effects of cowpea (Vignaunguiculata) andgroundnut (Arachis hypogea) on succeedingsorghum yields, soil mineral N and nematode infestation were studied during five cropping seasons (2000 to 2004) in a weakly acid Ultisol ofthe agronomy research station of Farakô-Ba located in the Guinean zone of Burkina Faso, WestAfrica. A factorial 5 × 5 design of five crop rotations with five fertilizer treatments in a split-plotarrangement with four replications was used.Sorghum yields were affected by the two factors(rotation with legumes and fertilizer applications)during the four years. But interactions were notobserved between the two factors. Monocropping of sorghum produced the lowest yields andlegume-sorghum rotations increased sorghumyields by 50% to 300%. Groundnut-sorghum andcowpea-sorghum rotations increased soil mineral N by 36% and 52%, respectively. Crop rotation influenced nematode infestation but theeffects on soil and sorghum root infestation differed according to the rotation. The cowpea sorghum rotation increased soil and sorghum root infestation by nematodes while groundnut-sorghum decreased the nematode population. Thesoil of the cowpea-sorghum rotation contained1.5 to 2 times more nematodes than the soil ofthe monocropping of sorghum. In contrast, thesoil of the groundnut-sorghum rotation contained from 17 to 19 times fewer nematodes thanthat of the monocropping of sorghum. However,nematode infestation did not affect any of thesucceeding sorghum yields. It was concludedthat the parasitic effect of nematodes was limited by the predominance of positive N-effectson the development of succeeding sorghum.